2012
DOI: 10.1038/cddis.2012.168
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targeting of NOX4 for neuropathic pain after traumatic injury of the spinal cord

Abstract: Neuropathic pain is a well-known type of chronic pain caused by damage to the nervous system. Until recently, many researchers have primarily focused on identifying cellular or chemical sources of neuropathic pain or have approached neuropathic pain via the basis of biological study. We investigated whether both mmu-mir-23b (miR23b) and NADPH oxidase 4 (NOX4) antibody infusion can alleviate neuropathic pain by compensating for abnormally downregulated miR23b via reducing the expression of its target gene, NOX4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…Animal models of neuropathic pain consist of evaluating pain sensitization after peripheral injury. A number of studies suggested a role of NOX-derived ROS in this process of nociceptive hypersensitization (39,80), but two studies addressed this question using genetically modified mice.…”
Section: Painmentioning
confidence: 99%
“…Animal models of neuropathic pain consist of evaluating pain sensitization after peripheral injury. A number of studies suggested a role of NOX-derived ROS in this process of nociceptive hypersensitization (39,80), but two studies addressed this question using genetically modified mice.…”
Section: Painmentioning
confidence: 99%
“…Neuropathic pain decreased with miR23b infusion that occurs as result of the NOX4 gene inactivated, where MiR23b protects GABAergic neurons against ROS/p38/c-JNK apoptotic cell death [61].A mouse model that utilized NOX4 and miR23b revealed both negative and positive impacts on neuropathic pain. Continually, Spinal nerve ligation (SNL) alters expression levels of miR-96, miR-182, and miR-183, suggesting that these molecules related to chronic neuropathic pain through translational regulation of painrelevant genes [62].…”
Section: Mirnas Therapy For Treating Neuropathic Painmentioning
confidence: 99%
“…[89][90][91][92][93] Some have successfully provided the proof-of concept for a role of specific miRNAs in influencing behavior using rodent models 79,94-96 (Fig. 4).…”
Section: Mirnas and Painmentioning
confidence: 99%